Study on performance of cabbage (Brassica oleraceae var. capitata L.) under different production systems - Elavarasan R; Somasundaram E; R. Krishnan; Suganthy M; Janaki P; Parameshwari E; Pradosh Kumar Parida; Parasuraman P (Plant Science Today, 2024)
Coimbatore is located in the western part of Tamil Nadu and nestled against the foothills of the Western Ghats. This region's cool climate and favourable terrain make it ideal for cultivating hill vegetables. Cabbage (Brassica oleracea var. capitata L.) is a significant cole crop known for its high nutritional value. Excessive chemical usage in cabbage cultivation leads to residual effects on soil and produce. This study aimed to identify the best production system for cabbage cultivation in the northwestern parts of Tamil Nadu. An experiment was conducted during the winter season of 2023-2024 at the Tamil Nadu Agricultural University, Coimbatore. The experiment was laid out in a randomized block design (RBD) with four treatments and five replications. The organic farming system exhibited the highest values for plant height (21.47 cm), stalk length (8.49 cm), dry matter accumulation (71.34 g per plant), days to head formation (18.75 days), days to harvest (56.25 days), head diameter (17.70 cm), head compactness (33.91), head weight (945.35 g per plant) and cabbage yield (24.92 t ha-1), surpassing both conventional and natural farming systems. A similar pattern was observed in quality parameters, including TSS (6.54 °Brix), shelf life (12.21 days) and ascorbic acid content (44.26 mg per 100 g). This study highlights an efficient cabbage cultivation system in the Coimbatore region, leading to improved yield, soil health and quality.